Prognostic value of clinical variables and liver histology for development of fibrosis and cirrhosis in autoimmune hepatitis. (4th March 2017) - Puustinen, Lauri; Boyd, Sonja; Mustonen, Harri; Arkkila, Perttu; Arola, Johanna; Färkkilä, Martti
Abstract: Objective: In autoimmune hepatitis, data on the prognostic value of baseline liver biopsy and the sequential histology is controversial. Our aim was to evaluate the prognostic value of clinical variables and biopsy at the time of diagnosis and during the disease course. Materials and methods: All 98 patients in our hospital during 1995–2012 were included. Sequential biopsies were available in 66 patients. Analyses based on clinical and histological variables were performed to find parameters predicting the progression of fibrosis, and development of cirrhosis. Results: At the time of diagnosis, 7% were cirrhotic. Fibrosis progressed in 28 (42%) patients, remained stable in 26 (39%) and resolved in 12 (18%) patients. Findings which predicted fibrosis progression, were baseline total inflammation (odds ratio 1.7, 95% CI 1.01–2.8), cumulative total inflammation (1.8, 95% CI 1.01–3.2, rosette formation (2.8, 95% CI 1.1–7.1), absence of pericholangitis (0.4, 95% CI 0.1–1.0) and necrosis (1.4, 95% CI 1.0–2.0). Risk factors for the development of cirrhosis were cholestasis (4.6, 95% CI 1.2–16.9), interphase inflammation (3.4, 95% CI 1.1–10.4), and necrosis (3.3, 95% CI 1.2–9.7). In a cumulative model, cumulative total inflammation (4.5, 95% CI 1.4–15.0), necrosis (6.7, 95% CI 1.3–34.6), or cumulative immunoglobulin G load (61.8, 95% CI 2.0–1954.3) were risk factors. None of the patients with histological pericholangitis or granulomas developed cirrhosis. Conclusions: The histology provides prognostic information regarding progression of fibrosis or the development of cirrhosis. The total cumulative inflammatory activity predicts the progression of fibrosis, whereas baseline fibrosis, interphase inflammation, cholestasis, necrosis, as well as the cumulative total inflammation and cumulative immunoglobulin G, are risk factors for cirrhosis.